2022
DOI: 10.3389/fpsyg.2022.843095
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Stressful Adjustment to Work: A Long-Term Prospective Study About Homeworking for Bank Employees in Italy

Abstract: The COVID-19 evolution has forced the massive introduction of homeworking (HW) for most employees in the initial stages of the pandemic and then return to work, mainly due to the vaccination campaign. These multiple abrupt adjustment demands in work may be a source of intense stress for office workers with consequences on wellbeing and the quality of life. This long-term prospective study aimed at investigating the effect of adaptation demands on a broad population of employees of a large Italian banking group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…As a consequence of a high strain on work-family conflict, a decrease in physical and mental health dimensions among women (including stress, anxiety, and depression symptoms) was reported in this study, as well as in previous research [ 19 , 23 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Both studies by Oakman et al [ 41 ] and Graham et al [ 39 ] showed that Australian working women reported significantly greater WFC and FWC, and concerns about job insecurity, stress, and neck/shoulder pain compared to men.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As a consequence of a high strain on work-family conflict, a decrease in physical and mental health dimensions among women (including stress, anxiety, and depression symptoms) was reported in this study, as well as in previous research [ 19 , 23 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Both studies by Oakman et al [ 41 ] and Graham et al [ 39 ] showed that Australian working women reported significantly greater WFC and FWC, and concerns about job insecurity, stress, and neck/shoulder pain compared to men.…”
Section: Discussionsupporting
confidence: 88%
“…Both studies by Oakman et al [ 41 ] and Graham et al [ 39 ] showed that Australian working women reported significantly greater WFC and FWC, and concerns about job insecurity, stress, and neck/shoulder pain compared to men. Furthermore, among home-working bank employees from Italy, women showed the greatest concerns for back-to-stationary work, WFC, and workaholism during the pandemic [ 42 ]. The number of children was correlated with a higher WFC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is evident as we captured the aftermath of the first vaccination round (September – December 2021) with case numbers declining, schools resuming in-person classes, and decreasing safety regulations in some places (i.e., no masks indoors and/or outdoors if vaccinated). In addition, there is evidence to suggest that the experience of the pandemic has changed over time ( Orfei et al, 2022 ). In our sample, the average for COVID-19 stress was a score of 15.14, though the possible range for stress was from 0 – 35.…”
Section: Discussionmentioning
confidence: 99%